2020
DOI: 10.1245/s10434-020-08905-9
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Response in Patients Undergoing Neoadjuvant Endocrine Treatment for Node-Positive Breast Cancer: Systematic Literature Review and NCDB Analysis

Abstract: Background. Several studies have proven that neoadjuvant endocrine therapy (NET) has a similar beneficial therapeutic effect in estrogen-positive (ER ?) breast cancer (BC) with improved breast conservation rate in patients undergoing NET versus neoadjuvant chemotherapy (NAC). The impact of axillary complete pathologic response (pCR) is less clear. We evaluate the impact of NET on axillary downstaging and surgical management. Methods. Using the National Cancer Database (NCDB), we identified all patients with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
1
25
2
1
Order By: Relevance
“…Similarly, Stafford et al studied patients from the NCDB during 2010–2016 with ER+/HER2– breast cancers treated with NET for > 30 days and reported a slightly higher axillary nodal pCR rate of 14.48% among 4580 patients staged as cN+. 27 They observed a higher likelihood of nodal pCR among patients with invasive ductal carcinoma, cN1 disease (75.9% of the study population), and grade II tumors. In that study, the duration of NET was unknown and patients with metastatic disease were included.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, Stafford et al studied patients from the NCDB during 2010–2016 with ER+/HER2– breast cancers treated with NET for > 30 days and reported a slightly higher axillary nodal pCR rate of 14.48% among 4580 patients staged as cN+. 27 They observed a higher likelihood of nodal pCR among patients with invasive ductal carcinoma, cN1 disease (75.9% of the study population), and grade II tumors. In that study, the duration of NET was unknown and patients with metastatic disease were included.…”
Section: Discussionmentioning
confidence: 88%
“…breast cancer, interest in this approach has been greatly accelerated by the COVID-19 pandemic and the rapid creation and adoption of guidelines for use of NET when surgery must be postponed. 4,18,27 Limitations of this study include its retrospective design without uniform selection criteria for NET, although patients were prospectively accrued. Additionally, longerterm follow-up will be important to further characterize FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A slight increase in these rates was observed by Rusz et al, reaching 13% node pCR in N+ patients after one year of NET with letrozole [ 31 ]. In a recent review, Stafford et al, after analyzing 4580 ER+ N+ breast cancers from the National Cancer Database, concluded that nodal pCR could be achieved in up to 14.5% of patients [ 32 ]. As reported by other authors, lobular breast cancer had a significantly lower percentage of nodal pCR when compared to ductal histologies (12.4% vs. 15.26%, p < 0.05) [ 32 , 33 ].…”
Section: Clinical Implications Of Netmentioning
confidence: 99%
“…In a recent review, Stafford et al, after analyzing 4580 ER+ N+ breast cancers from the National Cancer Database, concluded that nodal pCR could be achieved in up to 14.5% of patients [ 32 ]. As reported by other authors, lobular breast cancer had a significantly lower percentage of nodal pCR when compared to ductal histologies (12.4% vs. 15.26%, p < 0.05) [ 32 , 33 ]. Longer treatment duration (>6 months) seems to increase the likelihood of nodal pCR [ 24 , 31 ].…”
Section: Clinical Implications Of Netmentioning
confidence: 99%